Performance as a function of shooting style in basketball players under 11 years of age - Arias, J. L. (Perceptual and Motor Skills, 2012)
Shooting style in basketball refers to the height adopted by a player in holding the ball, specifically the height of the hand and the ball with regard to the line of sight before the final extension of the elbow during a shot. The literature differentiates between a high and a low style. This study analyzed shooting frequency in young boys as a function of style and which shooting style had the highest accuracy and success in real games. Participants were 81 boys from eight basketball teams, aged 9-11 years. The sample consisted of 5,740 standard shots in 56 games. The design was nomotethic, follow-up, and multidimensional. The results indicated that low style predominated over the high style, although overall accuracy and efficacy were better using the high style. Various strategies and practical considerations are suggested for teachers and coaches to focus on teaching the high style.